2012
DOI: 10.1089/end.2012.0037
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Blind and Nerve Stimulation Guided Obturator Nerve Block in Transurethral Resection of Bladder Tumor

Abstract: Transvesical ONB is a safe and effective method of ONB before TURBT. This method is feasible by urologists and promising even without nerve stimulation and only by anatomic landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…[1116] However, no complications were seen during our study as also reported by many other studies comparing blind, US-guided, and US nerve stimulator-guided ONB for transurethral surgery. [171626]…”
Section: Discussionmentioning
confidence: 99%
“…[1116] However, no complications were seen during our study as also reported by many other studies comparing blind, US-guided, and US nerve stimulator-guided ONB for transurethral surgery. [171626]…”
Section: Discussionmentioning
confidence: 99%
“…This nerve block may be performed by the guide of nerve stimulation or anatomic landmarks. [22][23][24] Moreover, more recent studies reported that the use of an ultrasound in regional anesthesia is associated with higher success rates as 93% to 97.2% in ultrasound-guided ONB procedures. 21,25 Akkaya and colleagues demonstrated a new methodological approach based on a sono-anatomic study to visualize the obturator nerve.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The pudendal nerve is called the social nerve because of its effect on bowel, sexual and bladder functions. Shafik et al demonstrated clinical and neurophysiological improvement in patients with interstitial cystitis following decompression of the pudendal nerves.…”
Section: Departments Of Pathology Urology and Oncologymentioning
confidence: 99%
“…Shafik et al demonstrated clinical and neurophysiological improvement in patients with interstitial cystitis following decompression of the pudendal nerves. 3 Voiding complaints occur in 58.5% of patients with pudendal neuropathy. Urge incontinence, frequency and painful bladder are improved or cured in more than 60% of the cases with pudendal nerve decompression by either a transgluteal or transperineal approach.…”
Section: Departments Of Pathology Urology and Oncologymentioning
confidence: 99%